1999
DOI: 10.1016/s0014-5793(99)01547-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of metabotropic glutamate receptor type 1c: a role for phosphorylation in the desensitization of the receptor

Abstract: The phosphorylation and desensitization of metabotropic glutamate receptor type 1c in response to agonist and phorbol esters has been studied. Specific immunoprecipitation of mGluR1c from cells treated with agonist or PMA showed a timedependent increase in the phosphorylation of a membrane protein with the same molecular weight as the dimeric form of the receptor. Measurements of inositol phosphate production showed a rapid functional desensitization of about 90% after agonist treatment, whereas treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…PKC is an important modulator of mGluR function (10,(13)(14)(15)(16)(17); however, the biochemical analyses characterizing the direct phosphorylation of mGluRs by PKC have been lacking. Therefore, we began to characterize the mGluR5 C terminus as the region most likely to contain PKC phosphorylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…PKC is an important modulator of mGluR function (10,(13)(14)(15)(16)(17); however, the biochemical analyses characterizing the direct phosphorylation of mGluRs by PKC have been lacking. Therefore, we began to characterize the mGluR5 C terminus as the region most likely to contain PKC phosphorylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…For example, activation of PKC by PMA induces a rapid loss of mGluR1a and -1b from the cell surface in BHK cells (Ciruela and McIlhinney, 1997). In addition, mGluR1c desensitizes in response to PKC phosphorylation (Ciruela et al, 1999). An- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to agonist-specific receptor desensitization, GPCR function can be regulated by agonist-independent heterologous mechanisms. For example, recent studies have demonstrated that protein kinase C (PKC) phosphorylates and regulates the desensitization and internalization of mGluR1a, -1b, and -1c (Ciruela and McIlhinney, 1997;Ciruela et al, 1999).…”
mentioning
confidence: 99%
“…This event seems to include a rapid component that may involve activation of protein kinase C (Catania et al, 1991;Thomsen et al, 1993;Alaluf et al, 1995;Ciruela et al, 1999a) and receptor internalization (Ciruela and McIlhinney, 1997;Doherty et al, 1999) and a slower, protein kinase C-independent component (Catania et al, 1991;Desai et al, 1996). Down-regulation of receptor 1…”
Section: Introductionmentioning
confidence: 99%
“…This event seems to include a rapid component that may involve activation of protein kinase C (Catania et al, 1991;Thomsen et al, 1993;Alaluf et al, 1995;Ciruela et al, 1999a) and receptor internalization (Ciruela and McIlhinney, 1997;Doherty et al, 1999) and a slower, protein kinase C-independent component (Catania et al, 1991;Desai et al, 1996). Down-regulation of receptor protein expression has been suggested to play a role in the latter process, because in cultured cerebellar granule cells, desensitization of the mGlu1 receptor has been shown to result in reduced levels of mGlu1 receptor mRNA upon exposure to glutamate or quisqualate or in the presence of high K ϩ concentration (Favaron et al, 1992;Aronica et al, 1993;Bessho et al, 1993).…”
mentioning
confidence: 99%